Pemanfaatan Biji Rambutan (Nephelium lappaceumL.) sebagai Biosorben Penyerapan Ion Logam Cd2+ dengan Metode Batch - Dewi, Shindy Mulia (journal of residu, 2019)
Biosorption is a method of using biomaterial-based materials as biosorbents and has the potential to be used in waste management that is environmentally friendly and low-cost. The purpose of this study is to determine the optimum conditions of absorption and maximum absorption capacity of rambutan seeds for Cd metal absorption. Absorption of heavy metal ions is influenced by pH, concentration, particle size, contact time and stirring speed, from each variation obtained the optimum conditions at pH 5 is 14.25 mg / g, concentration is 250 ppm, particle size is 90 µm, contact time 60 minutes. The interaction between adsorbents and adsorbates is determined using the Langmuir and Freudlich equations.At the stage of determining the biosorption isotherm of rambutan seeds with Cd metal ions in accordance with the Langmuir equation, with an R2 value of 0.9111